2019
DOI: 10.1371/journal.pone.0224011
|View full text |Cite
|
Sign up to set email alerts
|

Macro-charcoal accumulation in floodplain wetlands: Problems and prospects for reconstruction of fire regimes and environmental conditions

Abstract: Floodplain wetland ecosystems respond dynamically to flooding, fire and geomorphological processes. We employed a combined geomorphological and environmental proxy approach to assess allochthonous and autochthonous macro-charcoal accumulation in the Macquarie Marshes, Australia, with implications for the reconstruction of fire regimes and environmental conditions in large, open-system wetlands. After accounting for fluvial macro-charcoal flux (1.05 ± 0.32 no. cm-2 a-1), autochthonous macro-charcoal in ~1 m dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…Moreover, the absence of a relationship between the sediment grain size and charcoal storage in bedload suggests that the charcoal migration or accumulation occurs as an individual entity and is not co‐genetically linked with the process of the storage of pyrogenic biomolecules (Evan et al., 1990; Oen et al., 2006). The finer substrate plays a crucial role in carbon storage in the transient floodplain areas with limited variation in disturbance and modification through post‐depositional processes (Brown & Pasternack, 2004; Gao et al., 2017; Graves et al., 2019; Whitlock & Larsen, 2002). Such observation suggests that the higher finer sediment accumulation in the lowland floodplain can aid in the pre‐aging of charcoal and allows temporary storage of PyC across intermediate reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the absence of a relationship between the sediment grain size and charcoal storage in bedload suggests that the charcoal migration or accumulation occurs as an individual entity and is not co‐genetically linked with the process of the storage of pyrogenic biomolecules (Evan et al., 1990; Oen et al., 2006). The finer substrate plays a crucial role in carbon storage in the transient floodplain areas with limited variation in disturbance and modification through post‐depositional processes (Brown & Pasternack, 2004; Gao et al., 2017; Graves et al., 2019; Whitlock & Larsen, 2002). Such observation suggests that the higher finer sediment accumulation in the lowland floodplain can aid in the pre‐aging of charcoal and allows temporary storage of PyC across intermediate reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Natural transportation processes would impart a wide range of imposed energy as well as duration on charcoal particles during active hydrological transport across different geomorphic regimes of riverine transects (Crawford & Belcher, 2014; Graves et al., 2019). The stream power, discharge, slope, sediment load, resultant channel sinuosity and braid‐channel ratio have an integrated influence on the development of distinct geomorphic regimes and associated physical processes in fluvial environments (Bawa et al., 2014; Bizzi & Lerner, 2015; Sinha et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to what extent riparian systems were burned and with what regime is unknown (Enright and Thomas 2008). Nevertheless, it is unlikely that ubiquitous, widespread and severe burning like 2019-2020 has occurred before (Black and Mooney 2006;Mooney et al 2011;Graves et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of present-day African RF by our group showed that, within fewer than 40 years, bioturbation almost completely removes the initial stratigraphic evidence of how fields are constructed and maintained with the periodic addition of organic matter (Rodrigues et al 2020). In addition, archaeobotanical proxies can often under-represent certain crops (e.g., manioc produces few diagnostic phytoliths [Chandler-Ezell et al 2006]), may be affected by post-depositional modifications and taphonomic processes (e.g., macro-charcoal in wetlands [Graves et al 2019]), or are not even well preserved in tropical soils, as occurs with starch and pollen grains (Pearsall 2015).…”
Section: Introductionmentioning
confidence: 99%